An outflow powers the optical rise of the nearby, fast-evolving tidal disruption event AT2019qiz. Issue 1 (12th October 2020) - Nicholl, M; Wevers, T; Oates, S R; Alexander, K D; Leloudas, G; Onori, F; Jerkstrand, A; Gomez, S; Campana, S; Arcavi, I; Charalampopoulos, P; Gromadzki, M; et al.
ABSTRACT: At 66 Mpc, AT2019qiz is the closest optical tidal disruption event (TDE) to date, with a luminosity intermediate between the bulk of the population and the faint-and-fast event iPTF16fnl. Its proximity allowed a very early detection and triggering of multiwavelength and spectroscopic follow-up well before maximum light. The velocity dispersion of the host galaxy and fits to the TDE light curve indicate a black hole mass ≈10 6 M⊙, disrupting a star of ≈1 M⊙ . By analysing our comprehensive UV, optical, and X-ray data, we show that the early optical emission is dominated by an outflow, with a luminosity evolution L ∝ t 2, consistent with a photosphere expanding at constant velocity (≳2000 km s −1 ), and a line-forming region producing initially blueshifted H and He ii profiles with v = 3000–10 000 km s −1 . The fastest optical ejecta approach the velocity inferred from radio detections (modelled in a forthcoming companion paper from K. D. Alexander et al.), thus the same outflow may be responsible for both the fast optical rise and the radio emission – the first time this connection has been observed in a TDE. The light-curve rise begins 29 ± 2 d before maximum light, peaking when the photosphere reaches the radius where optical photons can escape. The photosphere then undergoes a sudden transition, first cooling at constant radius then contracting at constant temperature. At the same time, the blueshifts disappear from the spectrum and Bowen fluorescence lines (N iii ) become prominent, implying a source of far-UV photons, while the X-ray light curve peaks at ≈10 41 erg s −1 . Assuming that these X-rays are from prompt accretion, the size and mass of the outflow are consistent with the reprocessing layer needed to explain the large optical to X-ray ratio in this and other optical TDEs, possibly favouring accretion-powered over collision-powered outflow models.